An Exploratory Analysis of the Structure of Homework Assignments in High Schools - Joseph Murphy; Karen Decker; Carolyn Chaplin; Robyn Dagenais; Jerry Heller; Rosemary Jones; Marsha Willis (Journal of Research in Rural Education, 1987)
In this article we examine the structure of homework assignments in eight rural high schools. Seventy-seventeachers responded to a 36-item survey which was designed to assess (I) the amount of time students devote to homework; (2) the existence of a school homework policy; (3) the purpose and type of homework assignment; (4) teacher review, feedback, and grading of homework; and (5) the value and significance of assigning homework. Previous research in the area of homework has been limited to studies that investigate average hours of homework completed and correlations between time spent on homework and student achievement. Results presented in this article provide a deeper understanding of the structure and use of homework by rural high school teachers.